"Du må ha troen for å lykkes" - Broch, Harald Beyer (Tidsskrift for kulturforskning, 2016)
The article is based on material gathered during one year of continuous ethnographic fieldwork (2006-2007) and several revisits of shorter duration among North Norwegian fishermen. The methodological approach was primarily participant observation. The focus is on everyday fishing and fishing related activities. Analyzing how various practices are influenced by what is broadly defined as different beliefs, it is shown that ideas of magic influence appeal when it comes to explaining the unintelligible. Applying what is outlined as narrative theory, at the micro level of individuals, it is argued that we all live by the stories we tell each other and ourselves about the world. Thus in postmodern times it becomes problematic to separate knowledge from other forms of beliefs. That is not the claim of the fishermen among whom I worked, but a theoretical claim.